"Our Care through our eyes": impact of a co-produced digital education programme on nurses' knowledge, confidence and attitudes in providing care for children and young people who have self-harmed: a mixed-methods study in the UK - Manning, Joseph C.; Carter, Tim; Latif, Asam; Cooper, Joanne; Horsley, Angela; Armstrong, Marie; Crew, Jamie; Wood, Damien; Callaghan, Patrick; Wharrad, Heather (BMJ Publishing Group, 2017)
Objectives: 1. To determine the impact of a digital educational intervention on the knowledge, attitudes, confidence and behavioural intention of registered children’s nurses working with Children and Young People (CYP) admitted with self-harm 2. To explore the perceived impact, suitability and usefulness of the intervention.